Cross-multiplying, we get:
4(3) = x(sqrt(11) - 1)
12 = x(sqrt(11) - 1)
12 = xsqrt(11) - x
x = (12 + x)/sqrt(11)
x(sqrt(11)) = 12 + x
x(sqrt(11) - 1) = 12
x = 12/(sqrt(11) - 1)
Multiplying the numerator and denominator by the conjugate of the denominator, we get:
x = 12(sqrt(11) + 1)/(11 - 1)
x = 6(sqrt(11) + 1)/5
Therefore, the answer is (B) 6 over 5 square root 11 – 6 over 5.
10. Solve the proportion.
(Image: 4 over x = square root 11 – 1 over 3) (1 point)
(Image: 6 over 5 square root 11 – 6 over 5)
(Image: 5 over 6 square root 11 – 6 over 5)
(Image: 5 over 6 square root 11 + 6 over 5)
(Image: 6 over 5 square root 11 + 6 over 5)
1 answer